A Depth Chronicle of General English Learning at Non-English Major Students on Joyful Communication Activities - Fahmi Fahmi; Bayu Andika Prasatyo; Rasmita Rasmita; Kadnawi Kadnawi; Andini Linarsih; Rachmi Rachmi (Universitas Hamzanwadi, 2022)
Selecting joyful communication activities in English learning is indispensably essential. Undoubtedly, the students prefer joyful communication activities regardless the activities use assisted technology or not. Hence, this study sought to explore joyful communication activities based on EFL students' perceptions. It also aims to elicit students' attitudes toward technology-assisted and non-assisted communication activities. This study employed a mix-methods approach to obtain quantitative and qualitative data on 126 students from various non-English departments at a state university in Indonesia. Distributing the questionnaires was employed to obtain the quantitative data. Meanwhile, the qualitative data was obtained through semi-structured interviews. The findings show that three kinds of activities are recognized as the most joyful communication activities, and 12 are the medium of joyful communication activities. Furthermore, the other 16 activities are at a low position (not recommended). Regarding technology-assisted and non-assisted language learning, the student's attitude shows that they prefer to enjoy technology-non-assisted learning activities over technology-assisted activities. However, several activities using technology-assisted learning still gain students' attraction. The study suggests that lecturers should implement recognized joyful communication activities based on students' preferences for enhancing their interest in communication skill mastery.